Extremal properties, coefficient inequalities and radius properties of a certain class of close-to-convex functions / Abdullah Yahya - Yahya, Abdullah (2013)
Geometric function theory is a part of complex analysis which investigates the geometric properties of analytical functions. The study focuses on the class of analytic univalent function involving the complex plane. Let ₵ be the set of all complex numbers and let f(z) be a complex-valued function of the complex variable z . The derivative of f is defined as…(Continue)